The pure effect of social preferences on regional location choices: The evolving dynamics of convergence to a steady state population distribution - Oded Stark; Wiktor Budzinski; Grzegorz Kosiorowski (University of Tübingen, Faculty of Economics and Social Sciences, 2019)
This paper tracks the consequences of individuals' desire to align their location with their social preferences. The social preference studied in the paper is distaste for relative deprivation, measured in a cardinal manner. Location is conceived as social space, with individuals choosing to relocate if, as a result, their relative deprivation will be reduced, holding their incomes constant. Conditions are provided under which the associated dynamics reaches a spatial steady state, the number of periods it takes to reach a steady state is specified, and light is shed on the robustness of the steady state outcome. By way of simulation it is shown that for large populations, a steady state of the relocation dynamics is almost always reached, typically in one period, and that cycles are more likely to occur when the populations' income distributions are more equal.
urn:nbn:de:bsz:21-dspace-875563
Keywords: C62; C63; R12; R13; Z13; 330; Social preferences; Distaste for low relative income; A cardinal measure of income relative deprivation; Interregional locational choices; Relocation dynamics; Steady-state spatial distribution